2013
DOI: 10.1098/rsif.2012.0833
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic poly(ε-caprolactone)/iron-doped hydroxyapatite nanocomposite substrates for advanced bone tissue engineering

Abstract: In biomedicine, magnetic nanoparticles provide some attractive possibilities because they possess peculiar physical properties that permit their use in a wide range of applications. The concept of magnetic guidance basically spans from drug delivery and hyperthermia treatment of tumours, to tissue engineering, such as magneto-mechanical stimulation/activation of cell constructs and mechanosensitive ion channels, magnetic cell-seeding procedures, and controlled cell proliferation and differentiation. Accordingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(141 citation statements)
references
References 47 publications
5
134
1
1
Order By: Relevance
“…These composites also improve the cell spreading and the development of the actin cytoskeleton. 29 Similarly in our study, the cells on composites with nano-HA (particularly N15) showed relatively high concentrations of beta-actin, and also talin, which is a focal adhesion protein associated with the actin cytoskeleton. The beneficial effects of HA particles on the cell adhesion and growth were explained by the increased wettability of the composite material, changes in the material surface topography, improved adsorption of cell adhesion-mediating proteins to the material surface, and also the osteoinductive effect of HA.…”
mentioning
confidence: 76%
“…These composites also improve the cell spreading and the development of the actin cytoskeleton. 29 Similarly in our study, the cells on composites with nano-HA (particularly N15) showed relatively high concentrations of beta-actin, and also talin, which is a focal adhesion protein associated with the actin cytoskeleton. The beneficial effects of HA particles on the cell adhesion and growth were explained by the increased wettability of the composite material, changes in the material surface topography, improved adsorption of cell adhesion-mediating proteins to the material surface, and also the osteoinductive effect of HA.…”
mentioning
confidence: 76%
“…Soft and hard materials are susceptible to acquiring magnetic properties through the incorporation of magnetic iron oxide particles, as demonstrated in the development of magnetic hydrogels [85], magnetic bioactive glasses [86] magnetic blends of poly(caprolactone) (PCL)/hydroxyapatite [86], magnetic nanofibrous hydroxyapatite poly-lactide acid (PLA) [87],and magnetic PCL [88]. The methods for incorporation of magnetic particles in biomaterials include doping, blending, in situ precipitation, and the 'graftingonto' method [89].…”
Section: Magnetic Biomaterialsmentioning
confidence: 99%
“…To date, most published techniques have employed passive internalization of MNPs via endocytosis, which allows for effective magnetic modification of cells [11][12][13]. However, uptake of MNPs by cells entails several major drawbacks, such as (1) a lengthy internalization process, requiring up to 72 h of co-incubation of MNPs with cells [14,15] and (2) potential toxic effects of early-stage cytoplasminternalized nanoparticles [16].…”
Section: Introductionmentioning
confidence: 99%